Biodiversity of Clostridium botulinum Type E Strains Isolated from Fish and Fishery Products - Hyytiä, Eija (American Society for Microbiology, 1999)
The genetic biodiversity of Clostridium botulinum type E strains was studied by pulsed-field gel electrophoresis (PFGE) with two macrorestriction enzymes (SmaI-XmaI and XhoI) and by randomly amplified polymorphic DNA (RAPD) analysis with two primers (OPJ 6 and OPJ 13) to characterize 67 Finnish isolates from fresh fish and fishery products, 15 German isolates from farmed fish, and 10 isolates of North American or North Atlantic origin derived mainly from different types of seafood. The effects of fish species, processing, and geographical origin on the epidemiology of the isolates were evaluated. Cluster analysis based on macrorestriction profiles was performed to study the genetic relationships of the isolates. PFGE and RAPD analyses were combined and resulted in the identification of 62 different subtypes among the 92 type E isolates analyzed. High genetic biodiversity among the isolates was observed regardless of their source. Finnish and North American or North Atlantic isolates did not form distinctly discernible clusters, in contrast with the genetically homogeneous group of German isolates. On the other hand, indistinguishable or closely related genetic profiles among epidemiologically unrelated samples were detected. It was concluded that the high genetic variation was probably a result of a lack of strong selection factors that would influence the evolution of type E. The wide genetic biodiversity observed among type E isolates indicates the value of DNA-based typing methods as a tool in contamination studies in the food industry and in investigations of botulism outbreaks.